2018
DOI: 10.1021/acs.jchemed.7b00345
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Metals from Spent Screen-Printed Electrodes While Learning the Fundamentals of Electrochemical Sensing

Abstract: A laboratory experiment in which students recycle silver and platinum selectively from spent screenprinted platinum electrodes is described. The recovered silver in solution is used to show its spontaneous redox reaction with a copper sheet. The recovered platinum is electrodeposited onto a screen-printed carbon electrode to develop a sensor for hydrogen peroxide quantification in a commercially available hair lightener. The experiment is designed for a 3 h laboratory period and can be adapted for upper-divisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 16 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…The parameters usually optimized are separated in two main groups: The ones related to the precursor solution where the salt type and concentration are involved, and the conditions of electrochemical deposition. A list of usual salts employed are AgNO 3 [30][31][32][33][34] for silver NPs; HAuCl 4 [31,35,36] and AuCl 3 [37] for gold NPs; Bi(NO 3 ) 3 [16,38,39] for bismuth NPs; CoCl 2 [40] for cobalt NPs; CuCl 2 [41], CuSO 4 [42], and CuNO 3 [43,44] for copper NPs; NiCl 2 [40,45] and NiSO 4 [46,47] for nickel NPs; PdCl 2 [48][49][50] [30,[52][53][54][55][56], and PtCl 2 [37] for platinum NPs; RhCl 3 [57] for rhodium NPs, etc. Although higher concentrations of precursor allow bigger particles to be obtained, the size and shape are usually controlled electrochemically; so, the precursor concentration usually tends to be high enough to have sufficient material susceptible to be deposited and it is not often optimized [33].…”
Section: Methods Based On Electrochemical Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters usually optimized are separated in two main groups: The ones related to the precursor solution where the salt type and concentration are involved, and the conditions of electrochemical deposition. A list of usual salts employed are AgNO 3 [30][31][32][33][34] for silver NPs; HAuCl 4 [31,35,36] and AuCl 3 [37] for gold NPs; Bi(NO 3 ) 3 [16,38,39] for bismuth NPs; CoCl 2 [40] for cobalt NPs; CuCl 2 [41], CuSO 4 [42], and CuNO 3 [43,44] for copper NPs; NiCl 2 [40,45] and NiSO 4 [46,47] for nickel NPs; PdCl 2 [48][49][50] [30,[52][53][54][55][56], and PtCl 2 [37] for platinum NPs; RhCl 3 [57] for rhodium NPs, etc. Although higher concentrations of precursor allow bigger particles to be obtained, the size and shape are usually controlled electrochemically; so, the precursor concentration usually tends to be high enough to have sufficient material susceptible to be deposited and it is not often optimized [33].…”
Section: Methods Based On Electrochemical Depositionmentioning
confidence: 99%
“…Due to its good electrocatalytic activity towards peroxide, platinum can be used to detect this molecule in several real samples, such as cosmetics [53], household goods [30], or food and beverages [25], with good recoveries. A simple electrodeposition step is needed [37] to perform sensors with this method, affording a facile and robust methodology to monitor peroxide "in-situ" and making it even susceptible to academic demonstrations with hair lightener [56] and whitening strips [18] as real samples.…”
Section: As Sensing Phase For Other Analytesmentioning
confidence: 99%
“…With such modification, groups of 2–3 students could each be responsible for data collection with their own potentiostat and electrodes. We refer the interested reader to some of the many recent advances in course-based, inquiry-focused implementations of electrochemistry, electrochemical hardware, and electrodes , and plan several such undertakings ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…This is a key aspect of the United Nations Sustainable Goals, in which responsible consumption and production is a key aspect [10]. A variety of different waste materials have been used to fabricate electrodes such as disposed screen printed electrodes [11], quantitative filter paper and polyethene terephthalate (PET) from beverage bottles [8,9] and adhesive medical tape [12]. One interesting study carried out by Janegitz and co-workers [8] demonstrated that disposable electrodes can be easily prepared by modifying filter papers or PET with conductive inks to make electrode.…”
Section: Introductionmentioning
confidence: 99%